Decreased Cephalosporin Susceptibility of Oropharyngeal Neisseria Species in Antibiotic-using Men Who Have Sex With Men in Hanoi, Vietnam. (3rd May 2019) - Dong, Huan V; Pham, Loc Q; Nguyen, Hoa T; Nguyen, Minh X B; Nguyen, Trung V; May, Folasade; Le, Giang M; Klausner, Jeffrey D
Abstract: Background: Neisseria gonorrhoeae (NG) infections are a global health burden. NG resistance to cephalosporins, which is increasingly reported, is an imminent threat to public health. Many hypothesize that commensal Neisseria species are an important reservoir for genetic material conferring antimicrobial resistance in NG; however, clinical data are lacking. Methods: Men who have sex with men (MSM) in Hanoi, Vietnam, completed a questionnaire regarding antibiotic use. We collected pharyngeal specimens, cultured Neisseria species, and measured minimum inhibitory concentrations (MICs) to ciprofloxacin, cefixime, ceftriaxone, and cefpodoxime. Using MIC criteria for antimicrobial susceptibility in NG, we categorized the Neisseria species and compared mean MIC levels between different antibiotic user groups. Results: Of 207 participants, 38% used at least 1 antibiotic in the past 6 months; 52% without a prescription. A median of 1 Neisseria species was cultured from each participant (range, 1–4) with 10 different Neisseria species identified overall. The proportion of Neisseria with reduced susceptibility to ciprofloxacin was 93%, cefpodoxime 84%, cefixime 31%, and ceftriaxone 28%. Antibiotic use within the past month was strongly associated with Neisseria species having increased MICs to cefixime, ceftriaxone, and cefpodoxime (mean MIC ratios of 6.27, 4.11, and 7.70, respectively), compared with those who used antibiotics between 1 and 6 months prior ( P < .05, all comparisons). Conclusions: MSM in our study often used antibiotics without a prescription. At least 1 commensal Neisseria species colonized all men. Recent use of any antibiotics may select for oropharyngeal Neisseria species with antimicrobial resistance. The normal flora of the oropharynx may be an important source of antimicrobial resistance in Neisseria gonorrhoeae . Abstract : Commensal oropharyngeal Neisseria species show increased minimum inhibitory concentrations to extended-spectrum cephalosporins in recent antibiotic users and may be an important source of antibiotic resistance in pathogens such as N. gonorrhoeae .